Uji Aktivitas Antijamur Ekstrak Kulit Buah Kakao (Theobroma cacao L.) terhadap Candida albicans - Desy Sofyah Hartina; Yani Corvianindya Rahayu; Atik Kurniawati (Fakultas Kedokteran Gigi Universitas Jember, 2023)
Candidiasis is an opportunistic fungal infection caused by Candida albicans. The prevalence of candidiasis in Indonesia is around 20-25%, it can attack the skin, nails, hair, throat, and mouth. One of the fungal infections that occur in the oral cavity is oral candidiasis. Oral candidiasis is caused by overgrowth of Candida albicans species in the oral cavity which is dominated by Candida albicans as much as 85-95%. One of the treatments using herbal medicinal plants is cocoa peel containing active compounds including phenolics, flavonoids, tannins, and terpenoids which are thought to be antifungal. The aim was to determine the inhibition of cocoa peel extract on the growth of Candida albicans. This study used the disc diffusion method with 4 samples in each study group. The research group consisted of 5 treatment groups (10%, 20%, 40%, 80%, and 100% cocoa peel extract), positive control group (nystatin), and negative control group (sterile aquades). Data were analyzed using One Way Anova test and LSD (Least Significant Difference) test. Concentrations of extracts of cocoa pods 100% and 80% have the ability to inhibit the growth of Candida albicans.